2016
DOI: 10.1080/10942912.2016.1177071
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroactinidiolide from thermal degradation of β-carotene

Abstract: The formation of dihydroactinidiolide by thermal degradation of β-carotene was studied. A comparison of yields of dihydroactinidiolide in commercial β-carotene and β-carotene derived from crude palm oil was investigated. Thermal degradation of commercial β-carotene promoted the formation of dihydroactinidiolide with the highest yield, 61.21%. Thermal degradation of recovered β-carotene yielded 29.23% of dihydroactinidiolide. The lower recovery of β-carotene was due to the mixture of compounds in the extract. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…1 b. The study on degradation of $-carotene has been carried out in the last few decades where the degradation temperature has proposed start at 120EC 12 . The current result indicated that it would take time to degrade the carotenes from the crude extract of carrot when the degradation temperature was at 120EC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 b. The study on degradation of $-carotene has been carried out in the last few decades where the degradation temperature has proposed start at 120EC 12 . The current result indicated that it would take time to degrade the carotenes from the crude extract of carrot when the degradation temperature was at 120EC.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned by Hewavitharana et al 13 , the non-polar crude extract of foods consist of oils and fat fractions include triacylglycerol and sterols that have high degradation temperatures that is more than 140EC 14 . Some literature had suggested that the degradation temperature of $-carotene to form its derivative compounds was achieved around 140EC 12 . Furthermore, the accumulation of $-ionone and dhA was observed clearly from the product of degradation temperature of 140 and 160EC in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Safranal could increase the sweetness and had been identified as an aroma compound by GC-O (gas chromatography-olfactometry) in Pu-erh tea [14]. Dihydroactinidiolide could mask bad flavors and enhanced cigarette palatability [15]. Previous studies have demonstrated that microorganisms could degrade terpenoids into aromatic components.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, liquiritigenin is a chiral flavonoid with one or more stereogenic centers. Dihydroactinidiole is one of C11-terpene lactones which occur from the biological or degradation of carotenoids (Hamid et al 2017). This molecule was found to be a minor compound in P. haeundaensis SAB E11.…”
Section: Discussionmentioning
confidence: 99%